PAIR-WORK FOR SPEAKING CLASS FOR FORMAL INTERACTION IN UNIVERSITY - Yustina Putri, Amanda; Fitriya, Fitriya; Segoh, David (Department of Master of Linguistic, Universitas Airlangga, 2024)
This article contains students' pair work interactions on developing their speaking skills in speaking class. Pairing students for their speaking practice was more effective than grouping the students. But in this study that was not always the case. There are some requirements to complete the effectiveness of pair-work interaction. Thus, to collect the data, the author observed a speaking class in one of the universities in Surabaya with the consent of the faculty and the lecturer. The collected data will be analyzed using interactive analysis techniques and was presented in a descriptive form. There were two classes that were observed with 26 students in first class and 27 students in second class. When the students present are an odd number the lecturer will make it one group with three people. The lecturer lets the students have freedom to choose their own partner. The topic that was given to the students was